The Phenomenon of Foreign Migrations and Selected Aspects of the Development of Human Capital - Zdrojewski, Eugeniusz; Kisiel, Aneta (Olsztyn Economic Journal, 2017)
Certain regions or countries attract and succeed in retaining the existing demographic potential. Others undergo stagnation or even regress, which in extreme situations can lead to depopulation.This issue is important, as it is the inhabitants of given territories that initiate and create certain activities, values and changes in their environment. Today, attracting, retaining, developing and maintaining employees present a particularly difficult challenge, with migrations making it even more difficult. The paper addresses the issues of selected aspects of the development of human capital in the face of foreign migrations with Poland as an example. Human capital is shaped by multiple factors. Itis a complex process. The aim of this paper is to show the effects of foreign migrations in the practice of human resource management. On the one hand, management theoreticians and practitioners emphasize an increasing importance in the use of human capital; on the other hand, its waste can be seen in many situations.